Behind the Scenes of Instagram: The Relationship Between Self-Esteem and Narcissistic Tendencies Among Gen Z - Harod, Yabes Mahanaim; Goretti Adiyanti, Maria (Program Studi Psikologi, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2025)
The phenomenon of Gen Z's existence is beginning to increase on social media, potentially giving rise to narcissistic tendencies, especially about the level of self-esteem that individuals have. This study aims to analyze the relationship between self-esteem and narcissistic tendencies in Gen Z on Instagram social media. The study used a quantitative approach with a correlational design, with a purposive sampling technique involving 148 Gen Z participants who actively use Instagram social media. Data collection was conducted using the Coopersmith Self-Esteem Inventory (CSEI) and the Narcissism on Social Media Scale (NSMS). The results of data analysis using Spearman correlation, showed a significant negative relationship between self-esteem and narcissistic tendencies (r = -0.645, p < 0.05). The lower the self-esteem, the higher the narcissistic tendencies on Instagram social media, and vice versa. The findings reinforce the view that narcissistic tendencies are often used as a compensation mechanism for low self-esteem. This study provides practical implications to help Gen Z understand the importance of improving self-esteem to prevent maladaptive narcissistic tendencies on social media.Fenomena eksistensi Gen Z mulai meningkat di media sosial, berpotensi memunculkan kecenderungan narsistik, terutama berkaitan dengan tingkat self-esteem yang dimiliki individu. Penelitian ini bertujuan untuk menganalisis hubungan antara self-esteem dengan kecenderungan narsistik pada Gen Z di media sosial Instagram. Penelitian menggunakan pendekatan kuantitatif dengan desain korelasional, dengan teknik purposive sampling yang melibatkan 148 partisipan Gen Z yang aktif menggunakan media sosial Instagram. Pengumpulan data dilakukan menggunakan Coopersmith Self-Esteem Inventory (CSEI) dan Narcissism on Social Media Scale (NSMS). Hasil analisis data menggunakan korelasi Spearman, menunjukkan adanya hubungan negatif yang signifikan antara self-esteem dan kecenderungan narsistik (r = -0,645, p < 0,05). Semakin rendah self-esteem, semakin tinggi kecenderungan narsistik di media sosial Instagram, dan sebaliknya. Temuan memperkuat pandangan bahwa kecenderungan narsistik sering dijadikan mekanisme kompensasi atas self-esteem yang rendah. Penelitian ini memberikan implikasi praktis yang dapat membantu Gen Z dalam memahami pentingnya meningkatkan self-esteem untuk mencegah kecenderungan narsistik yang maladaptif di media sosial.